URINARY BLADDER WALL STRUCTURAL ELEMENTS REACTION OF MATURE RATS TO THE IMPACT OF THE GENERAL DEEP HYPOTHERMIA DURING LATER TERMS - Popadynets, O.H. (World of Medicine and Biology, 2012)
The results of complex study of urinary bladder wall (intraorganic blood vessels, membranes, intramural vegetative plexus) and pro- and antioxidant systems morphofunctional condition during later terms of posthypothermic period (during the 7th, 14th and 30th days), which was performed in the experiment at 21 mature male rats, weight 160-180 g (7 animals – control group), were presented in this work. In studied structures during the 7th day the dystrophic-destructive changes were found, during 14th day there were compensatory-adaptive manifestations, which further contributed the restorative processes, and we observed them during the 30th day. Such dynamics of morphologic changes associates with peroxidation processes and antioxidant systems activation.